2022
DOI: 10.3389/fcimb.2022.1007950
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis identifies HPV-related tumor microenvironment remodeling prognostic biomarkers in head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinomas (HNSCCs) are highly aggressive tumors with rapid progression and poor prognosis. Human papillomavirus (HPV) infection has been identified as one of the most important carcinogens for HNSCC. As an early event in HNSCC, infection with HPV leads to altered immune profiles in the tumor microenvironment (TME). The TME plays a key role in the progression and transformation of HNSCC. However, the TME in HNSCC is a complex and heterogeneous mix of tumor cells, fibroblasts, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…In addition, the up‐regulated expression of PLAU was associated with HPV positivity and the neck node status 50 . ITGA5, PLAU, PLAUR, SERPINE1 and TGFB1 have potential as prognostic biomarkers for HNSCC mediated by HPV infection 48 . Expression of PLAU in HNSCC was also detected by immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, the up‐regulated expression of PLAU was associated with HPV positivity and the neck node status 50 . ITGA5, PLAU, PLAUR, SERPINE1 and TGFB1 have potential as prognostic biomarkers for HNSCC mediated by HPV infection 48 . Expression of PLAU in HNSCC was also detected by immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 96%
“…PLAU has been associated with the prognosis of patients with head and neck cancer. [47][48][49][50] In a HNSCC bioinformatics study, PLAU, SERPINE1, and ACTA1 were linked to the prognosis of patients. Among them, the labelling score of PLAU significantly 51 In the present study, we attempt to detect changes in PLAU protein expression due to P. gingivalis infection and found a transient increase of PLAU protein (Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bioinformatics tools have been widely used to identify novel molecular markers of cancer. In HNSCC, many scholars use bioinformatics methods to identify biomarker candidates for diagnosis and prognosis, such as the biomarkers of tumour-infiltrating lymphocytes and HPVrelated tumour microenvironment remodelling [30][31][32]. However, the biomarkers obtained from bioinformatics represent only the starting point, further experimental and functional studies would have to be performed in order to validate their predictive role [33].…”
Section: Discussionmentioning
confidence: 99%
“…Pei et al developed a hypoxia risk score model based on SERPINE1 revealing the correlation between hypoxia and tumor immune microenvironment ( Pei et al, 2021 ). In addition, numerous studies published in the past few decades reported that SERPINE1 is one of the most reliable biomarkers and prognostic markers in many cancer types, including breast cancer ( Harbeck et al, 2004 ; Palmirotta et al, 2009 ; Duffy et al, 2014 ; Duffy et al, 2016 ; Jevrić et al, 2019 ), ovarian cancer ( Mashiko et al, 2015 ; Nakatsuka et al, 2017 ), renal cell carcinoma ( Ahluwalia et al, 2021 ), head and neck squamous cell carcinoma ( Pavón et al, 2015 ; Guo et al, 2022 ; Zhou et al, 2022 ; Li et al, 2023 ), bladder cancer ( Chan et al, 2017 ), colorectal cancer ( Sakakibara et al, 2005 ), gastric cancer ( Khan et al, 2022 ; Xu et al, 2022 ) and non-small cell lung cancers ( Sotiropoulos et al, 2019 ). Previous studies also demonstrated that SERPINE1 can promote cancer progression and metastasis as it is promoting the tumor migration, invasion, and angiogenesis ( Dellas and Loskutoff, 2005 ; Li et al, 2018 ; Kubala and DeClerck, 2019 ).…”
Section: Introductionmentioning
confidence: 99%